Post-Processing Thermal Activation of Thermoelectric Materials Based on Germanium - Piotr Marek Markowski; Eugeniusz Prociów (Energies)
After the deposition process, the lattice structure of doped germanium remains low. Post-processing annealing reorders the structure and increases the output parameters. Thin films of germanium doped with gold (Ge:Au) and vanadium (Ge:V) were magnetron-sputtered on glass substrates. The course of the activation process was monitored in situ. Two different methods of post-processing thermal activation of the films were studied. The first method was to place the structure at an elevated temperature for a specified period of time. The second method involved placing the structure on a heating table and cycling the heating and cooling several times from room temperature to about 823 K. Both methods fulfill their function well. The differences come down to research aspects. The best thermoelectric parameters were achieved for germanium doped with 0.95 at.% vanadium. The Seebeck coefficient of 212 μV/K and the power factor of 1.24 mW·m−1·K−2 were obtained at 500 K.